2018
DOI: 10.1038/s41467-018-04111-0
|View full text |Cite|
|
Sign up to set email alerts
|

Bcl11b is essential for licensing Th2 differentiation during helminth infection and allergic asthma

Abstract: During helminth infection and allergic asthma, naive CD4+ T-cells differentiate into cytokine-producing Type-2 helper (Th2) cells that resolve the infection or induce asthma-associated pathology. Mechanisms regulating the Th2 differentiation in vivo remain poorly understood. Here we report that mice lacking Bcl11b in mature T-cells have a diminished capacity to mount Th2 responses during helminth infection and allergic asthma, showing reduced Th2 cytokines and Gata3, and elevated Runx3. We provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 62 publications
(85 reference statements)
4
51
0
Order By: Relevance
“…5A), similarly to conventional CD4 + T cells ( 28 ). In line with our previous observations in conventional CD4 + T cells ( 28 ), motif analysis showed that the top 2 motifs were ETS (E26 transformation-specific) and Runx (Runt-related transcription factor) (fig. S4).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…5A), similarly to conventional CD4 + T cells ( 28 ). In line with our previous observations in conventional CD4 + T cells ( 28 ), motif analysis showed that the top 2 motifs were ETS (E26 transformation-specific) and Runx (Runt-related transcription factor) (fig. S4).…”
Section: Resultsmentioning
confidence: 92%
“…We further performed Bcl11b chromatin immunoprecipitation sequencing (ChIP-seq) analysis on T reg cells to identify genes directly controlled by Bcl11b, which we compared with Bcl11b genomic binding in naïve CD4 + T cells ( 28 ). Given that numerous genes regulated by Bcl11b are also known Foxp3 targets, we also compared the genomic binding by Bcl11b with Foxp3 binding in T reg cells ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological SIRT1 inhibition contributed to decreased allergic inflammation in BALB/c mice exposed to ovalbumin via aerosol (40). In addition, mice that exhibit KO of a transcriptional activator essential for Th2 differentiation (B-cell lymphoma/leukemia 11B; Bcl11b) have been found to be protected against EAE (41). Bcl11b is a transcriptional repressor and likely functions by recruiting SIRT1 for histone deacetylase activity (42).…”
Section: Effector Cd4+ T Cellsmentioning
confidence: 99%